2021
DOI: 10.21070/jbmp.v6i2.1514
|View full text |Cite
|
Sign up to set email alerts
|

Halal Risk Priority In Food Supply Chain Manajemen Based On A Technology Perspective

Abstract: Halal is a main requirement for Muslims in food selection. On the other hand, the increasing Muslim population in the world also encourages an increase in the availability of halal food. In its development, driven by technological advances, there is a risk of changes in halal food. These changes can occur in the food supply chain that involves various aspects. This study aims to identify risks based on technological aspects (technoware, humanware, infoware, orgaware). Furthermore, this study also aims to prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Prior studies have highlighted digital technology's role in improving transparency, integrity, and certification processes in the halal industry, thereby establishing international best practices alongside mainstream food industry sectors. Information technology has been identified as a factor that can improve performance and efficiency and expand supply chain networks in the context of HSC management [19]. Additionally, the adoption of halal warehousing has been found to be significantly influenced by technological factors, emphasizing the importance of compatibility and perceived benefits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have highlighted digital technology's role in improving transparency, integrity, and certification processes in the halal industry, thereby establishing international best practices alongside mainstream food industry sectors. Information technology has been identified as a factor that can improve performance and efficiency and expand supply chain networks in the context of HSC management [19]. Additionally, the adoption of halal warehousing has been found to be significantly influenced by technological factors, emphasizing the importance of compatibility and perceived benefits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on supply chain risk identification has been widely carried out, such as analyzing risks using the fuzzy FMEA method [29][30], identifying risks and analyzing food safety risks using the SCOR method [31,32], identifying halal risks using the AHP method [33], assessing halal risks using the FMEA method [34], and mitigating risks using the integration of SCOR, HOR, and AHP [35]. Previous research is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%